KAJIAN KEAMANAN PANGAN JAJANAN ROTI DI TOKO ROTI KECAMATAN BINJAI KOTA DAN BINJAI UTARA TAHUN 2014 - CHRISNA AYUNINGTIAS; Ernawati Nasution; jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Food safety is the things that make the food product is safe to eat , free from factors that can cause disease . The role of food safety is very important because food security is a prerequisite for a food , unsafe food can cause illness . The research was purposed determine to study food safety bread snacks bakery in Binjai City and North Binjai District. This is a descriptive study . Samples were taken was 60 of 20 snacks bread bakery. The research variabels were the completeness of the labeling, the characteristics of the bread and food additives. This research was an observasional method for labeling and completeness characteristics of bread and qualitative analysis of the use of food additives Test Kit . The results of observational studies labeling on bread snacks in the District of North Binjai and Binjai City that 65.0 % have included labels on packaging and general information listed on the label is the name and address of the production as well as the registration number . Observation of the characteristics of bread after 2 days showed 40.0 % experienced discoloration or moldy , 55.0 % have a hard texture , 40.0 % had a rancid aroma . Based on qualitative tests on food additives from 20 shows 16.7 % butter sandwich using dye methanyl Yellow , 37.5 % using the dye Rhodamine B , 45 % use the sweetener cyclamate and the entire snack bread using a preservative Potassium Bromate . Expected to Binjai City Health Department and the Agency for Drug and Food control , to be more active to provide counseling and guidance to manufacturers of food packaging products to meet the food labeling regulations and crack down on manufacturers who violate this regulation . Keywords        : food safety , bread snacks